FRENCH DISCOURSE ANALYSIS AND CONVERSATIONAL ANALYSIS - Rustamova Feruzabonu Ilkhomovna; Rasulova Shahinabonu (Bright Mind Publishing, 2025)
This article presents a comparative analysis of the French School of Discourse Analysis and Conversational Analysis. Despite their shared goal—the study of language in its social context—these approaches differ in their scale of analysis, research focus, and methodological tools. The French School, represented by the works of Pêcheux, van Dijk, and others, focuses on the macro-level, analyzing ideological and power relations reflected in large discursive formations. Conversational Analysis, conversely, examines the micro-level, detailing the organization and structure of everyday conversations.
Keywords: Discourse analysis, conversational analysis, context, micro-level, macro-level.